PENGARUH CITRA TOKO TERHADAP KEPUTUSAN PEMBELIANKONSUMEN PADA MINIMARKET ALFAMART KAMAL - TRIWAHYUDI A, DAFED (Jurnal Ilmu Manajemen (JIM), 2013)
Kamal Alfamart success is determined by several things,the first is the image, these factors are related to the company’soverall image is formed through interaction in the form of helpingconsumers identify a brand and differentiate it from other brands. Thisresearch is conclusive research. The population in this study iscustomer at Kamal Alfamart minimarket. Samples taken as many as136 people with accidental sampling technique. Measuring instrumentused a questionnaire, and the data were analyzed with multiple linearregression. The results of t test, store image variables which consistsof: place, product, price, customer service, promotion, and physicalfacilities influence partially and between all variables, product giveshighes influence.Keywords: purchasing decision, store image.